PENGEMBANGAN LIFE SKILL SOCIETY 5.0 SANTRI DI PONDOK PESANTREN DARUL ULUM REJOSO KAB. PASURUAN - Lutfi, Muhammad Khoirul (Center of Education Journal (CEJou), 2024)
This research describes and explores the educational system of the Pondok Pesantren Darul Ulum Karangpandan in Pasuruan in developing Society 5.0 life skills. With a strong virtual interaction model and digital leadership, the Pondok Pesantren Darul Ulum Karangpandan in Pasuruan is still considered capable of preparing excellent skills in line with the Society 5.0 era. The research employs a descriptive approach and focuses on: 1. How the educational system of the Pondok Pesantren Darul Ulum Karangpandan Rejoso Pasuruan develops Society 5.0 life skills for its students. 2. The implementation of developing Society 5.0 life skills for students at the Darul Ulum Karangpandan. 3. Supporting and inhibiting factors in the development of Society 5.0 life skills for students at the Pondok Pesantren Darul Ulum Karangpandan Pasuruan. Efforts by the Pondok Pesantren Darul Ulum to enhance its presence in the current Society 5.0 era involve maximizing learning facilities, optimizing teaching and learning processes, developing curricula, cultivating students' life skills through extracurricular programs, and improving the quality of teachers and students who are digitally adept, collaborative, innovative, and productive. Supporting factors in the development of students' Society 5.0 life skills include establishing strategic partnerships with digital industries and social institutions, the roles of the religious leaders (kiai) and the family council, alumni involvement, and the digital-based learning systems and media in the madrasah. On the other hand, inhibiting factors include the school's somewhat closed learning system and the nascent quality assurance of digital learning. Keyword: Life Skill Society 5.0, Santri, Pondok Pesantren